Superparamagnetic nanoparticles for synthesis and purification of polymers prepared via controlled/"living" radical polymerization (CLRP) - Saoud, Fozi (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2010.